An Analysis of Students’ Writing Anxiety in English Learning at Grade XII MIPA 3 of SMAN 6 Padang (e-Journal of Linguistics, 2023)
This study aims to analysis of students’ writing anxiety in English learning atSMAN 6 Padang grade XII MIPA 3. This research is qualitative. The techniques ofcollecting data are Questionnaire and interview. The subject of this research was36 students’ of XII MIPA 3. The purpose of this research is analyzed what factorscause students to be anxious about writing in English learning in grade XII MIPA3 SMAN 6 Padang. The results of the data that have been obtained with thecognitive problems is the factors that most influence students’ anxiety in writingEnglish especially in grade XII MIPA 3 at SMAN6 Padang, and from internalfactors influencing students’ anxiety in writing English factor problem of wordchoice has the lowest score from internal factors in writing English classroom, itscores was 31.86%. And from external factors lowest score is lack of knowledgeabout writing stages, it score was 32.03%
Keywords: Students’ anxiety; students’ writing; anxiety problem; writing anxiety; sampling technique